Contribution to the knowledge of Patagonia, Argentina: Redescription of the genus Xenogenus Berg 1883 (Hemiptera: Heteroptera: Rhopalidae) and description of immature stages of Xenogenus gracilis Reed, 1899 - Diez, Fernando (2015)
This is a review of Xenogenus Berg 1883 a Neotropical genus with two species: X. gracilis Reed (1899) and X. picturatum Berg 1883. Males of X. picturatum, males and females of X. gracilis are redescribed and illustrated; instars II-V of X. gracilis are described and illustrated. The host plant and new record data are also given for the latter.